2000
DOI: 10.1002/1522-2594(200011)44:5<713::aid-mrm9>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Displacement imaging of spinal cord using q‐space diffusion‐weighted MRI

Abstract: Displacement MR images of water in in vitro rat spinal cord were computed from q-space analysis of high b value diffusion-weighted MRI data. It is demonstrated that q-space analysis of heavily diffusion-weighted MRI (qs-DWI) provides MR images in which physical parameters of the tissues such as the mean displacement and the probability for zero displacement of the water molecules are used as contrasts. It is shown that these MR images provide structural information surpassing the spatial resolution of conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(128 citation statements)
references
References 25 publications
9
117
2
Order By: Relevance
“…It is thereby possible to characterise complex systems, for example, situations where the diffusion is restricted to confinements. In nuclear magnetic resonance (NMR), q-space analysis is widely used to study porous media [13] and q-space imaging in a clinical setting was first introduced by Assaf et al [14]. The q-space technique might be valuable for studies of brain pathologies, including ischemic stroke, neurodegenerative diseases like various forms of dementia [15] and Parkinson's disease as well as white matter degeneration like in multiple sclerosis (MS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is thereby possible to characterise complex systems, for example, situations where the diffusion is restricted to confinements. In nuclear magnetic resonance (NMR), q-space analysis is widely used to study porous media [13] and q-space imaging in a clinical setting was first introduced by Assaf et al [14]. The q-space technique might be valuable for studies of brain pathologies, including ischemic stroke, neurodegenerative diseases like various forms of dementia [15] and Parkinson's disease as well as white matter degeneration like in multiple sclerosis (MS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that the structural information obtained from the diffusion-diffraction dips and from the PDF obtained by the Fourier transform (FT) of the signal decay, were the same [21]. This is important since q-space diffusion MR, which had been used to study red blood cells [22,23] has recently been used to study neuronal tissue and WM in the central nervous system, both in vitro and in vivo [24][25][26][27][28][29][30][31][32]. In these cases, diffractions were not observed, probably due to the distribution of axon sizes [18,27,33].…”
Section: Introductionmentioning
confidence: 66%
“…Bar-Shir, Y. Cohen / Journal of Magnetic Resonance 190 (2008) [33][34][35][36][37][38][39][40][41][42] on the bulk ADC values obtained from low b-value diffusion NMR. Since diffraction patterns are generally not apparent in neuronal tissues [29][30][31][32][33]37], in contrast to what we found for uniform micro-cylinders [34], we focused on the rms displacement extracted from the FWHH of the displacement distribution profiles obtained. In addition, in a uniform micro-cylinders study [34], only a single Gaussian was needed to fit the data, whereas in the present study, bi-Gaussian functions were needed to fit the experimental data.…”
Section: Discussionmentioning
confidence: 97%
“…The q-space approach, originally developed by Callaghan [24] and by Cory and Garroway [25], was subsequently proposed as a means to obtain structural information from high b-value (high q) diffusion MR data in neuronal tissues [26][27][28][29][30][31]. This approach was extended to MRI and was first used to study structures and pathologies in isolated organs using strong gradient systems [29,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation